2016
DOI: 10.1371/journal.pone.0166331
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Cataract Is Associated with Elevated Serum Immunoglobulin E Levels in the South Korean Population: A Cross-Sectional Study

Abstract: BackgroundPrevious research has suggested that immunoglobulin E (IgE)-mediated events lead to several chronic diseases. We investigated the association between allergic conditions and age-related cataracts in the South Korean adult population.MethodsA cross-sectional study was performed using data obtained from 1,170 participants aged 40 years or older who were enrolled in the Korean National Health and Nutrition Examination Survey 2010. Multivariable logistic regression was used to examine the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…This is not much different from the study of Yoo et al in South Korea who get a senile cataract prevalence of 34%. 7 In the group of subjects with senile cataracts the mean age of the patients was 64.00 ± 10.36 years with the most age group being 61-70 years (40%). The prevalence of senile cataracts will increase rapidly with age.…”
Section: Discussionmentioning
confidence: 93%
“…This is not much different from the study of Yoo et al in South Korea who get a senile cataract prevalence of 34%. 7 In the group of subjects with senile cataracts the mean age of the patients was 64.00 ± 10.36 years with the most age group being 61-70 years (40%). The prevalence of senile cataracts will increase rapidly with age.…”
Section: Discussionmentioning
confidence: 93%
“…27,28 Ram et al 29 reported that patients with lower levels of C3 are recognized to be more susceptible to infection. The C3-mediated immune response may be a major trigger of systemic inflammation and systemic inflammation is involved in the progression of ARC 26,30,31 ; we hypothesized that ARC patients tend to be more susceptible to infection, which can cause a further decrease in serum C3. Schaumberg et al 30 reported that baseline C-reactive protein was significantly higher among men who later developed cataract than levels among those who remained free of cataract, and indicated that systemic inflammation may play a role in the pathogenesis of ARC.…”
Section: Discussionmentioning
confidence: 99%
“…Three common indoor allergens were tested for house dust mite ( Dermatophagoides farina ), cockroach and dog. Those with total IgE levels >100 kU/L were categorized as having “increased IgE” 14 , 15 , and those with allergen-specific IgE levels ≥0.35 kU/L were considered sensitized 11 .…”
Section: Methodsmentioning
confidence: 99%